Impact of thermal oxidation pressure and temperature on deactivation of the interfacial trap states in Al2O3/GaAs MOS capacitor. Issue 9 (13th May 2015) - Lim, Hajin; Kim, Seongkyung; Kim, Joon Rae; Song, Ji Hun; Lee, Nae‐In; Jeong, Jae Kyeong; Kim, Hyeong Joon
Abstract : Although GaAs is one of the most attractive channel materials for achieving high electron mobility, reduction of the interface state is still required for high quality MOS devices. In this paper, thermal oxidation under two pressures and various temperatures, and subsequent HF etching were performed to deactivate the interfacial states of the Al2 O3 /GaAs stack. High pressure oxidation (HPO) at 10 atm and 400 °C resulted in substantial improvement in the C – V frequency dispersion characteristics whereas the deactivation effect of the interfacial trap density under the thermal oxidations at 1 atm was not observed irrespective of the thermal oxidation temperature, ranging from 400 to 550 °C. Strong disparity between pressure and temperature was elucidated based on the existence of an efficient As excess layer and the prevention of unwanted Ga oxidation.